Burnout among Community Corrections Officers: Do Supervisor and Coworker Support Matter?. Issue 2 (15th March 2021) - Mack, Kristin Y.; Rhineberger-Dunn, Gayle
ABSTRACT: The purpose of this study was to evaluate factors that predict burnout among community corrections staff, with a particular focus on the impact of supervisor and coworker support. Using the Maslach Burnout Inventory, we evaluated the impact of supervisor and coworker support, individual attributes, job characteristics, and workplace perceptions on emotional exhaustion, depersonalization, and personal accomplishment among our sample of nearly 300 probation/parole and residential officers. Additionally, we assessed which set of variables (support, individual/job characteristics, or workplace perceptions) had the greatest impact on each measure of burnout. Our results indicated that supervisor support negatively impacted emotional exhaustion and depersonalization, but that coworker support was not significant for any of the three burnout measures. Additionally, models predicting emotional exhaustion and depersonalization were somewhat similar, whereas the personal accomplishment model was significantly different. Lastly, workplace perception variables had a stronger influence than individual/job characteristics or social support variables on all three burnout components. However, social support had a greater impact than individual/job characteristics for depersonalization and personal accomplishment.